KONJAC GLUCOMANNAN AS FOAM STABILIZER IN POLYHERBAL DRINK POWDER VIA FOAM MAT DRYING - Hamad, Alwani; Putra, Dimas Dwisardi; Sundhani, Elza; Hartanti, Dwi (Food and Feed Research, 2025)
The polyherbal drink contains polyphenol compounds that have many health benefits. The water extract of polyherbal drinks in the liquid phase has a short shelf life. Further powder processing is desirable by simple methods such as foam mat drying, that depend on the foam stabilizer. Konjac glucomannan (KGM) solution has the potential as a foam stabilizer. This study investigated the effect of konjac glucomannan concentrations (0-1%) as a foam stabilizer on polyherbal drink powder's physicochemical properties and antioxidant activity in foam mat drying. The polyherbal drink foam was prepared by adding lecithin at 10% w/w as a foaming agent and KGM as a foam stabilizer. The foam characters e.g Foam Expansion (FE), Air Fraction (AF), and Foam Stability (FS), and the powder characters, including physical and chemical (Total phenolic content (TPC) and Total Flavonoid content (TFC)), were investigated. Moreover, the powder's antioxidant activity was also analyzed using The DPPH free radical scavenging and Ferric Reduction Antioxidant Power (FRAP) methods. The results showed that applying KGM improved the stability of foam at a concentration of 0.5% upwards (FS>92.32%; FE>1.51). However, the physical properties of the powder were unchanged. All powders showed constant TPC (1.16- 1.36 mg GAE/g) and TFC (13.21- 28.92 mg QE/g). In addition, all powders revealed similar antioxidant activity both in DPPH free radical scavenging (231-245 mM TE/g) and FRAP (141-154 mM TE/g). The utilization of KGM as a foam stabilizer in the foam mat drying process demonstrated improved foam stability, particularly when used at a concentration of 0.5%.
Keywords: herbal drink; java tea; turmeric; seed-under-leaf; foam mat drying